Utility of Combined Echocardiography and Lung Ultrasound for Coronavirus Disease-19 Intensive Care Unit Patients: Case Series - Bosevski, Marijan; Janusevski, Filip; Kapsarov, Kosta (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: A little evidence existed for ultrasound evaluation of coronavirus disease (COVID)-19 patients. AIM: We aimed to present combined transthoracic echocardiography and lung ultrasound in 17 COVID-19 patients in the intensive care unit (ICU). METHODS: Patients were on age 57 + 14 years, 9 on mechanical ventilation and 8 on oxygen support, with average 1.2 comorbidities per patient. Ultrasound was performed by a single experienced sonographer and an assistant. RESULTS: Impaired left ventricular ejection fraction (EF) was found in 2 patients (pts) of them (11.8%) and diastolic dysfunction in 7 (41.2%), which was significantly higher in those ones with comorbidities. In 2 pts (11.8%), the presence of pulmonary hypertension with enlarged right ventricle was found. Later one pulmonary thromboembolism was confirmed in them with computed tomography angio. B-lines were found in 8 pts (47.1%), finding that was significantly higher in pts on mechanical ventilation, but not in relation with decreased EF. In one pt (0.6%), pleural effusion was found, but in none of them lung consolidation. CONCLUSIONS: Our findings revealed that combined echocardiography and lung ultrasound in COVID-19 ICU pts have been an accurate method for diagnosing right and left ventricular function and should be a useful one for guiding of their treatment and prognosis.